Seeded Growth of Au@CuxO Core–Shell Mesoporous Nanospheres and Their Photocatalytic Properties - Zhang, Gongguo; Ma, Yanyun; Liu, Feng; Tong, Zhibo; Sha, Jingquan; Zhao, Wenjun; Liu, Maochang; Zheng, Yiqun (Frontiers in Chemistry, 2021)
We report a facile synthesis of Au@CuxO core–shell mesoporous nanospheres with tunable size in the aqueous phase via seeded growth. The success of the current work relies on the use of a halide-free copper (Cu) precursor and n-oleyl-1,3-propanediamine as a capping agent to facilitate the formation of a copperish oxide shell with a mesoporous structure and the presence of mixed oxidation states of Cu. By varying the amount of spherical Au seeds while keeping other parameters unchanged, their diameters could be readily tuned without noticeable change in morphology. As compared with commercial Cu2O, the as-prepared Au@CuxO core–shell mesoporous nanospheres exhibit the higher adsorption ability, enhanced activity, and excellent stability toward photocatalytic degradation of methyl orange (MO) under visible light irradiation, indicating their potential applications in water treatment.